(untitled) (The Research of Medical Science Review, 2025)
Background: Coronary artery disease (CAD) is a leading cause of cardiovascular morbidity and mortality worldwide, primarily driven by elevated low-density lipoprotein cholesterol (LDL-C). Although statins are the first-line therapy for lipid lowering, many patients fail to achieve optimal LDL-C targets with monotherapy alone. Ezetimibe, when combined with statins, offers an additive effect by inhibiting intestinal cholesterol absorption. Objectives: To compare the efficacy of fixed-dose rosuvastatin plus ezetimibe combination therapy versus rosuvastatin monotherapy in patients with coronary artery disease. Study Design & Setting: A randomized controlled trial was conducted in the Department of Internal Medicine, Rawalpindi Teaching Hospital (RTH), Rawalpindi from 1st December 2024 to 1st May 2025. Methodology: A total of 154 patients with established CAD and LDL-C >100 mg/dL were randomized into two equal groups (n=77). Group I received rosuvastatin 10 mg daily, while Group II received a fixed-dose combination of rosuvastatin 10 mg and ezetimibe 10 mg daily. Lipid profiles were assessed at baseline, 12 weeks, and 24 weeks. Efficacy was defined as a ≥50% reduction in lipid parameters (LDL-C, TC, TG, HDL-C) from baseline. Results: At 24 weeks, Group II showed significantly greater reductions in LDL-C (52.3% vs. 36.2%), TC (34.6% vs. 24.0%), TG (33.9% vs. 23.5%), and a higher increase in HDL-C (23.3% vs. 8.1%) compared to Group I (p<0.001). Efficacy was achieved in 74.0% of patients in Group II versus 37.7% in Group I (p<0.001). Conclusion: Fixed-dose rosuvastatin plus ezetimibe therapy was significantly more effective than rosuvastatin monotherapy in achieving lipid profile targets in CAD patients